2021
DOI: 10.1155/2021/6650670
|View full text |Cite
|
Sign up to set email alerts
|

New Biomarker in Chagas Disease: Extracellular Vesicles Isolated from Peripheral Blood in Chronic Chagas Disease Patients Modulate the Human Immune Response

Abstract: Chagas disease, a neglected tropical disease (NTD) caused by the flagellated protozoan Trypanosoma cruzi (T. cruzi), is a major public health problem. It was initially restricted to Latin America, but it is now expanding globally. Host and pathogen interactions are crucial in the establishment of disease, and since 1970, it has been known that eukaryotic cells release extracellular vesicles (EVs), which in turn have an important role in intercellular communication in physiological and pathological conditions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 60 publications
(43 reference statements)
4
31
0
Order By: Relevance
“…In the field of Chagas disease and EVs, most scientific works has focused on the identification of new molecules from vesicles released by different stages of T. cruzi parasites cultured in vitro (Bautista‐López et al 2017; Bayer‐Santos et al, 2013; Ribeiro et al, 2018). Only two papers have reported analyses on the purification and characterization of circulating EVs, in blood from patients with CCD, using SEC (Jung et al, 2012) or ultracentrifugation for purifying EVs (Madeira et al, 2021) as stand‐alone methodologies. In the present study and following recent recommendations (Coumans et al, 2017; Thery et al, 2018), we have combined ultracentrifugation followed by SEC to purify circulating EVs from CCD patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the field of Chagas disease and EVs, most scientific works has focused on the identification of new molecules from vesicles released by different stages of T. cruzi parasites cultured in vitro (Bautista‐López et al 2017; Bayer‐Santos et al, 2013; Ribeiro et al, 2018). Only two papers have reported analyses on the purification and characterization of circulating EVs, in blood from patients with CCD, using SEC (Jung et al, 2012) or ultracentrifugation for purifying EVs (Madeira et al, 2021) as stand‐alone methodologies. In the present study and following recent recommendations (Coumans et al, 2017; Thery et al, 2018), we have combined ultracentrifugation followed by SEC to purify circulating EVs from CCD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Three milliliters of plasma or serum were centrifuged for 18 h at 100,000 g (Thermo Scientific™ Sorvall™ WX100 Ultra Centrifuge) using a fixed angle rotor (Thermo Scientific™ T‐8100 Fixed Angle Rotor). The supernatant was discarded, and the pellet was resuspended in 100 µl of 0.45 µm filtered phosphate‐buffered saline (PBS), as described (Madeira et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Madeira et al, 2021, observed a lower concentration of circulating EVs associated with differential activation of the immunological system in patients with chronic Chagas disease, with increased production of IFN-g, when compared with uninfected healthy controls (Madeira et al, 2021). This data was associated with parasite persistence suggesting that the EVs can be potential candidates as biomarkers during the course of Chagas disease.…”
Section: Role Of Evs From T Cruzi (Evst) In the Imunne System Modulationmentioning
confidence: 96%
“…Circulating EVs of chronic CD patients are similar in size but have lower concentrations than those of healthy individuals. Additionally, stratification of CD patients revealed that a reduction in EV concentration is associated with the severity of cardiac clinical parameters (Madeira et al, 2021). These differences may be related to differential release or retention of EVs in the tissues during disease progression, which may be a marker or contributor to CD pathogenesis.…”
Section: Evs Obtained From the Blood Of CD Patientsmentioning
confidence: 99%